PENERAPAN STRATEGI PEMBELAJARAN TANDUR UNTUK MENINGKATKAN SELF-EFFICACY SISWA PADA MATERI SUHU DAN KALOR KELAS X SMA NEGERI 14 PEKANBARU - Trisya Afidah Sukma; Zuhdi Ma’ruf; Azizahwati ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : This research aims to determine the increase of student’s self-efficacy in class X SMAN 14 Pekanbaru by applying the TANDUR strategies on subject Temperature and Heat. The research was conducted in SMAN 14 Pekanbaru precisely in February 2016 to June 2016. The form of the research is one group pretest-posttest design. The research instruments used include: (1) questionnaires of self-efficacy, and (2) observation sheet self-efficacy. Data analysis is conducted by using Gain self-efficacy through questionnaires given to the students of class X3 before and after the implementation of TANDUR strategies. The observation is conducted by observing the students on every meeting. The results of this research: (1) After the implementation of the TANDUR strategies, self-efficacy of students has increased based on questionnaire score obtained gain value 0,30; (2) based on the observation values increased from 55,68% to 74,05% in the medium category. The result of this research indicate that the results of questionnaires and observations can be concluded that the implementation of TANDUR strategies that have been applied to the class X3 SMAN 14 Pekanbaru can be improve the self-efficacy of the students in the learning of physics.Key Words : TANDUR strategies, self-efficacy, temperature and heat.